Delete : the virtue of forgetting in the digital age - Mayer-Schönberger, Viktor (Princeton University Press, 2009)
Looks at the surprising phenomenon of perfect remembering in the digital age, and reveals why we must reintroduce our capacity to forget. This title traces the important role that forgetting has played throughout human history, from the ability to make sound decisions unencumbered by the past to the possibility of second chances.